PEMANFAATAN SUSU SKIM SEBAGAI BAHAN DASAR DALAM PEMBUATAN PRODUK OLAHAN MAKANAN TRADISIONAL DANGKE DENGAN BANTUAN BAKTERI ASAM LAKTAT - Gemy Nastity Handayani; Nur Ida; Ahmad Rusmin R (Universitas Islam Negeri Alauddin Makassar, 2014)
Dangke is Enrekang traditional food products, which is a kind of cheese products without curing, and not coagulated with rennet but with papain (papaya latex). Dangke in this formula made using skim milk base material which is then fermented using bacteria Lactobacillus bulgaricus and Streptococcus thermophillus which has been commonly used in the manufacturing process of milk fermentation. The purpose of this study was to determine the quality of processed food products made from the traditional Dangke basic ingredients of skim milk, and skim milk determine the effect of concentration and fermentation time on making dangke to dangke generated. Research methods include making Dangke with 3 variations of the concentration of skim milk 5%, 10%, 15%, heating at a temperature of 65ºC. 40ºC cooling, inoculation with bacteria Lactobacillus bulgaricus and Streptococcus thermophillus. Incubation temperature of 40.5°C in the oven. In the incubation period 1, 2, 3 days organoleptic testing in the form of color, aroma, flavor, and texture analysis is then performed fat, protein, and lactic acid. The results of the analysis showed that the organoleptic quality of processed food products traditional Dangke made from basic ingredients in the manufacture of skim milk yield dangke dangke white, flavored lactic acid, sour, textured semi-solid. The results of the analysis indicate that the nutritional value of the higher concentration of skim milk and the longer the fermentation time caused the increase in protein content, total lactic acid and a decrease in fat content. The conclusion of this study is skim milk can be used as an alternative raw material in the manufacture dangke. Effect of skim milk concentration and fermentation time on the quality of dangke can increase total levels of lactic acid, protein content and lower fat content. Fermentation dangke better quality than the conventional dangke.